Hígado graso no alcohólico como factor de riesgo de preeclampsia en gestantes atendidas en el Hospital Regional de Loreto periodo 2020 a 2023 - Castillo la Torre, María Grazia (2025)
A study will be carried out to determine if non-alcoholic fatty liver disease is a risk factor for preeclampsia in pregnant women treated at the Hospital Regional of Loreto period 2020 to 2023, through an analytical, observational, retrospective cohort study; in a population of pregnant women treated in the Obstetrics Service of the Hospital Regional of Loreto during the period 2020 to 2023, reaching a number of 596 patients; for the statistical analysis, the information collected will be tabulated and the results of the instruments used will be interpreted; frequency distribution data will be obtained for the qualitative variables; the chi-square statistic will be used; significance will be considered if the chance is less than 5% (p < 0.05), and relative risk and multivariate analysis.